2021
DOI: 10.3390/nu13113699
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Analysis Reveals That Unsubstituted β-Ring and C8-Keto Structures Are Important Factors for Anti-Inflammatory Activity of Carotenoids

Abstract: Carotenoids are natural lipophilic pigments with substantial health benefits. Numerous studies have demonstrated the anti-inflammatory activities of carotenoids, especially toward lipopolysaccharide-induced inflammatory responses. As such, there are few reports on the evaluation and comparison of the anti-inflammatory activities of carotenoids against inflammation induced by other stimuli. In this study, we used pathogen-associated molecular patterns, proinflammatory cytokines, degenerated proteins, and chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 40 publications
1
7
0
1
Order By: Relevance
“…Studies performed on the transfected human monocytic cell line, which was treated with siphonaxanthin at 1.0 µM concentration for 24 h, showed the anti-inflammatory effect of this carotenoid, manifested by the significant inhibition of the LPS-and TNF-α-induced NFκB activation. Moreover, pretreatment with siphonaxanthin at 1.0 µM concentration significantly suppressed the IL-1β-induced NFκB activation [117]. Ganesan et al [113] revealed that siphonaxanthin might inhibit FGF-2 signaling.…”
Section: Siphonaxanthinmentioning
confidence: 99%
“…Studies performed on the transfected human monocytic cell line, which was treated with siphonaxanthin at 1.0 µM concentration for 24 h, showed the anti-inflammatory effect of this carotenoid, manifested by the significant inhibition of the LPS-and TNF-α-induced NFκB activation. Moreover, pretreatment with siphonaxanthin at 1.0 µM concentration significantly suppressed the IL-1β-induced NFκB activation [117]. Ganesan et al [113] revealed that siphonaxanthin might inhibit FGF-2 signaling.…”
Section: Siphonaxanthinmentioning
confidence: 99%
“…The delivery of neurotrophic compounds by nanocarriers and the targeted recovery of neurons are important strategies to improve the neurotherapeutic efficacy, and specific self-assembled nanomaterials have good neuroprotective properties, safety, and efficacy . For example, the recently reported liquid crystal nanocarriers are potential alternatives to the emerging delivery systems for fucoxanthin. , Compared to other carotenoids, such as siphonaxanthin, β-carotene, astaxanthin, and neoxanthin, as the main active ingredient in major dietary algae, fucoxanthin has also been reported to have anti-inflammatory, antioxidant, antitumor, antidiabetic, antiangiogenic, and neuroprotective activities. Among them, its neuroprotective properties have received extensive attention in recent years. , Previous research has shown that fucoxanthin can be used as a neurotrophic supplement to protect nerve cells and increase synaptic plasticity by modulating oxidative stress, alleviating inflammatory responses, improving dopamine secretion, and promoting neurotrophin expression. , …”
Section: Introductionmentioning
confidence: 99%
“…4 For example, the recently reported liquid crystal nanocarriers are potential alternatives to the emerging delivery systems for fucoxanthin. 5,6 Compared to other carotenoids, such as siphonaxanthin, 7 β-carotene, 8 astaxanthin, 9 and neoxanthin, 10 as the main active ingredient in major dietary algae, fucoxanthin has also been reported to have anti-inflammatory, antioxidant, antitumor, antidiabetic, antiangiogenic, and neuroprotective activities. Among them, its neuroprotective properties have received extensive attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have been revealing the action of carotenoids as inflammatory modulators. In a study by Manabe et al (2021) for example, it was found that TNF-α-induced activation of NF-κB and IRFs was significantly inhibited by βcarotene (-28% and -45%, respectively). This author further states that circulating leukocytes, especially monocytes, are considered an important source of pro-inflammatory cytokines, as monocytes receive inflammatory stimuli, numerous pro-inflammatory genes are induced mainly by activation of nuclear factor kappa B (NF-κB) and interferon regulatory factors (IRFs).…”
Section: Introductionmentioning
confidence: 99%